Economic Development and Modernization in Africa Homogenize National Cultures - Minkov, Michael; Kaasa, Anneli; Welzel, Christian (Journal of cross-cultural psychology, 2021)
The nation-building literature of the early 1960s argued that decolonized countries need to overcome pre-colonial ethnic identities and generate national cultures. Africa is the most critical test case of this aspect of modernization theory as it has by far the largest ethnolinguistic fractionalization. We use data from the Afrobarometer to compare the cultures of 85 ethnolinguistic groups, each represented by at least 100 respondents, from 25 African countries. We compared these groups and their nations on items that address cultural modernization and emancipation: ideologies concerning inclusive-exclusive society (gender egalitarianism, homophobia, and xenophobia), submissiveness to authority, and the societal role of religion. Previous research has shown that these are some of the most important markers of cultural differences in the modern world. Hierarchical cluster analysis yielded very homogeneous national clusters and not a single ethnolinguistic cluster cutting across national borders (such as Yoruba of Benin and Yoruba of Nigeria, Ewe of Ghana, and Ewe of Togo, etc.). Only three ethnolinguistic groups (3.5%) remained unattached to their national cluster, regardless of the clustering method. The variation between nations (F values) was often considerably greater than the variation between ethnolinguistic groups. Medial distances between the groups of each country correlated highly with GDP per person (r = −.54), percentage men employed in agriculture (r = .64), percentage men employed in services (r = −.63), and phone subscriptions per person (r = −.61). In conclusion, economic development and modernization diminish cultural differences between ethnolinguistic groups within nations, highlighting those between them.